Municipal sewage advanced treatment material and preparation method thereof
By using three-dimensional composite aerogel materials in urban sewage treatment, combined with the adsorption mechanism of nanofiltration layer and Mg-HA nanosheets, the problem of removing negatively charged pollutants and metal ions in sewage is solved, and efficient and economical pollutant removal effect is achieved, improving the safety of water environment and human health.
Patent Information
- Application Number
- CN202510238833.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-04-11
AI Technical Summary
The removal efficiency of negatively charged pollutants and metal ions in urban sewage is limited, which has threatened the safety of the water environment and human health.
Using a combination of physical and chemical adsorption method, a nanofiltration layer on the surface of a three-dimensional composite aerogel, a two-dimensional network formed by polyaspartic acid-grafted 4-acetylamino-TEMPO oxidized nanocellulose, and Mg-HA intercalated nanosheets formed in the aerogel framework are used to achieve efficient adsorption of urban wastewater.
It has achieved efficient removal of negatively charged pollutants and metal ions in urban sewage, improved the safety of water environment and human health, and has a high specific surface area and a multi-stage pore structure, enhancing the adsorption capacity.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of water treatment, and in particular to a material for deep treatment of urban sewage and a preparation method thereof. Background Art
[0002] With the acceleration of urbanization, the amount of urban sewage discharge has increased year by year, and its composition has become increasingly complex. In addition to traditional organic pollutants and nutrients, emerging pollutants such as negatively charged pollutants and metal ions have become increasingly prominent, posing a serious threat to water environment safety and human health. These pollutants come from a wide range of sources, including industrial wastewater, domestic sewage, agricultural runoff, etc. They are of various types and properties, bringing huge challenges to water environment management. Negatively charged pollutants have the characteristics of stable structure and difficulty in degradation, and tend to persist in the water environment. These pollutants can be enriched through the food chain, and ultimately endanger human health, interfere with the endocrine system, induce cancer, etc. For example, azo dyes in dye wastewater are carcinogenic, antibiotics in PPCPs can lead to increased bacterial resistance, and PFCs can affect the reproductive system and immune system. In addition, negatively charged pollutants (such as anionic surfactants, nitrate ions and sulfate ions) can also affect the balance of aquatic ecosystems, inhibit photosynthesis of aquatic plants, and reduce the self-purification capacity of water bodies. Metal ions are highly toxic and easily accumulated, and can cause harm to aquatic organisms and humans even at low concentrations. For example, lead can damage the nervous system, especially causing irreversible effects on children's intellectual development; cadmium can cause kidney damage; mercury can damage the brain and nervous system, causing "Minamata disease"; chromium can induce cancer, especially hexavalent chromium, which is highly carcinogenic. Metal ions are difficult to degrade in the water environment and will continue to accumulate through the food chain, eventually posing a serious threat to human health. Traditional urban sewage treatment processes mainly target organic pollutants and nutrients, and have limited removal efficiency for negatively charged pollutants and metal ions. In recent years, researchers have made significant progress in new adsorption materials, advanced oxidation technologies, and membrane separation technologies. For example, nano-adsorption materials with high specific surface area and rich surface functional groups have been developed, which can efficiently adsorb and remove negatively charged pollutants in water; advanced oxidation technologies such as Fenton oxidation, ozone oxidation, and photocatalytic oxidation can mineralize difficult-to-degrade organic pollutants into carbon dioxide and water; and membrane separation technologies such as nanofiltration and reverse osmosis can effectively intercept metal ions in water. These new technologies provide new ideas and methods for the efficient removal of negatively charged pollutants and metal ions in urban sewage. In short, the hazards of negatively charged pollutants and metal ions in urban sewage cannot be ignored. It is necessary to strengthen the research on their sources, migration and transformation laws, and eco-toxicological effects, and develop efficient, economical and environmentally friendly removal technologies to provide technical support for ensuring water environment safety and human health. In addition, deep treatment of urban recycled water and its differentiated utilization can provide an effective way to increase revenue and reduce expenditure for saving water resources. Summary of the invention
[0003] Technical problem to be solved: The purpose of the present invention is to provide a material for deep treatment of urban sewage and a preparation method thereof, which adopts a method combining physical and chemical adsorption, utilizes the nanofiltration layer on the surface of three-dimensional composite aerogel, the two-dimensional network formed by 4-acetylamino-TEMPO oxidized nanocellulose grafted with polyaspartic acid, and the Mg-HA intercalated nanosheets formed in the aerogel skeleton to achieve efficient adsorption of urban sewage.
[0004] Technical solution: A material for deep treatment of urban sewage, characterized in that: the material is a three-dimensional composite aerogel, the surface of the three-dimensional composite aerogel has a nanofiltration layer with a positive charge, the three-dimensional composite aerogel uses polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide as a skeleton, the polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose is a two-dimensional network structure, and the skeleton is loaded with calcium hydroxide and magnesium hydroxide nanosheets. Preferably, the method for preparing the three-dimensional composite aerogel comprises the following steps: S1. adding polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide into water, and stirring the solution to homogenize; S2. Add the ball-milled limestone tailing particles to the solution obtained in S1, add an alkaline solution to adjust the pH of the solution to 7-8, and obtain a mixed solution by ultrasonic dispersion; S3. freeze-drying the solution obtained in S2 to obtain an initial aerogel; S4. The initial aerogel obtained in S3 is immersed in an acidic polyurea-polyguanamine solution, and a three-dimensional composite aerogel having a positively charged nanofiltration layer on the surface is obtained by electrostatic crosslinking. Preferably, the mass ratio of the polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose to polyacrylamide in S1 is 1-5:1-3, and the mass fraction of the homogenous solution is 4-12wt%. Preferably, the preparation method of polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose in S1 comprises the following steps: S11. adding 4-acetylamino-TEMPO oxidized nanocellulose, polyaspartic acid and N-hydroxysuccinimide to water, and stirring to obtain a homogeneous solution A; S12. Add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to solution A, adjust the pH value of the solution to 4-6 at room temperature, react for 3-7 hours, wash and freeze-dry, and obtain polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose. Preferably, the mass ratio of 4-acetylamino-TEMPO oxidized nanocellulose, polyaspartic acid and N-hydroxysuccinimide in S11 is 6-8:2-3:0.01-0.015, and the mass fraction of the homogeneous solution is 2-10wt%. Preferably, the mass of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in S12 is 10-15wt% of the 4-acetylamino-TEMPO oxidized nanocellulose in S11. Preferably, the particle size of the ball-milled limestone tailings in S2 is 300-600 nm, the mass of the ball-milled limestone tailings is 10-15 wt % of the polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide, and the alkaline solution is one or more of sodium bicarbonate solution, sodium carbonate solution or ammonia solution. Preferably, the freeze-drying temperature in S3 is -50 to -40°C and the time is 18 to 24 hours. Preferably, the concentration of the acidic polyurea-polyguanamine solution in S4 is 5-20 g / L, the pH of the acidic polyurea-polyguanamine solution is 5-7, the thickness of the nanofiltration layer is 70-100 μm, and the pore size is less than 2 nm. Beneficial effects: The present invention has the following advantages: 1. In the present invention, polyaspartic acid is grafted onto 4-acetylamino-TEMPO oxidized nanocellulose, and the disulfide bonds in the polyaspartic acid are covalently grafted onto the 4-acetylamino-TEMPO oxidized nanocellulose, thereby obtaining 4-acetylamino-TEMPO oxidized nanocellulose grafted with two-dimensional network polyaspartic acid. The two-dimensional network structure has a high specific surface area and directional pores, and exhibits certain advantages in metal ion adsorption. The carboxyl group (-COOH) and amino group (-NH2) in the molecular structure of polyaspartic acid can form stable chelates with metal ions, and the polyaspartic acid has certain antibacterial properties, which plays a role in sterilizing recycled water. 2. The calcium carbonate in the limestone tailing particles in the three-dimensional composite aerogel skeleton of the present invention is dissolved in an alkaline solution, and the released calcium ions combine with phosphate ions to reach a supersaturated state, thereby promoting the nucleation and growth of HA nanosheets; in addition, the amino (-NH2) or carboxyl (-COOH) functional groups on the polyacrylamide molecular chain in the aerogel skeleton can combine with calcium ions (Ca 2+ ) interact with each other to form a template structure, guide the nucleation and growth of HA nanosheets, and arrange them in a specific direction to form nanosheets; and the magnesium carbonate in the limestone tailings particles dissolves in the alkaline solution, and forms Mg-intercalated HA nanosheets during the nucleation and growth of HA nanosheets, i.e., Mg-HA nanosheets; the Mg-HA nanosheets have a multi-level pore structure and are embedded in the aerogel, and cooperate with the pores of the aerogel itself to achieve the adsorption of negatively charged pollutants; 3. The three-dimensional composite aerogel in the present invention is immersed in an acidic polyurea-polyguanamine solution, and the polyacrylamide in the aerogel skeleton is electrostatically cross-linked with the polyurea-polyguanamine to obtain a three-dimensional composite aerogel with a positively charged nanofiltration layer on the surface. The positively charged nanofiltration layer achieves the adsorption of negatively charged pollutants in urban sewage through electrostatic adsorption. DETAILED DESCRIPTION The present invention will be further described below in conjunction with embodiments, which are explanations of the present invention and are not limited to the following embodiments: Example 1 A material for deep treatment of urban sewage, characterized in that: the material is a three-dimensional composite aerogel, the surface of the three-dimensional composite aerogel has a positively charged nanofiltration layer, the nanofiltration layer is obtained by electrostatic crosslinking of polyacrylamide and polyurea-polyguanamine, the three-dimensional composite aerogel uses polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide as a skeleton, the polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose is a two-dimensional network structure, and the skeleton is loaded with calcium hydroxide and magnesium hydroxide nanosheets; The method for preparing the three-dimensional composite aerogel comprises the following steps: S1. adding polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide in a mass ratio of 1:1 into water, and stirring to obtain a homogeneous solution with a mass fraction of 4 wt %; S2. Adding ball-milled limestone tailing particles with a particle size of 300 nm to the solution obtained in S1, the mass of the ball-milled limestone tailing particles is 10 wt % of the polyaspartic acid-grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide, adding sodium bicarbonate solution to adjust the solution pH to 7, and obtaining a mixed solution by ultrasonic dispersion; S3. freeze-dry the solution obtained in S2 at -50 °C for 18 h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 is immersed in an acidic polyurea-polyguanamine solution having a concentration of 5 g / L, wherein the pH of the acidic polyurea-polyguanamine solution is 5, and a three-dimensional composite aerogel having a positively charged nanofiltration layer on the surface is obtained by electrostatic crosslinking, wherein the nanofiltration layer has a thickness of 70 μm and a pore size of less than 2 nm; The method for preparing polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose in S1 comprises the following steps: S11. adding 4-acetylamino-TEMPO oxidized nanocellulose, polyaspartic acid and N-hydroxysuccinimide in a mass ratio of 6:2:0.01 to water, and stirring to obtain a homogeneous solution A with a mass fraction of 2 wt %; S12. Add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to solution A. The mass of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 10wt% of the 4-acetylamino-TEMPO oxidized nanocellulose in S11. Adjust the pH value of the solution to 4 at room temperature. After reacting for 3 hours, wash and freeze-dry to obtain polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose. Example 2 A material for deep treatment of urban sewage, characterized in that: the material is a three-dimensional composite aerogel, the surface of the three-dimensional composite aerogel has a positively charged nanofiltration layer, the nanofiltration layer is obtained by electrostatic crosslinking of polyacrylamide and polyurea-polyguanamine, the three-dimensional composite aerogel uses polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide as a skeleton, the polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose is a two-dimensional network structure, and the skeleton is loaded with calcium hydroxide and magnesium hydroxide nanosheets; The method for preparing the three-dimensional composite aerogel comprises the following steps: S1. adding polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide in a mass ratio of 5:3 to water, and stirring to obtain a homogeneous solution with a mass fraction of 12 wt %; S2. Add limestone tailing particles with a particle size of 600 nm to the solution obtained in S1, wherein the mass of the ball-milled limestone tailing is 15 wt % of the polyaspartic acid-grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide, add sodium carbonate solution to adjust the solution pH to 8, and obtain a mixed solution by ultrasonic dispersion; S3. freeze-dry the solution obtained in S2 at -40 °C for 24 h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 is immersed in an acidic polyurea-polyguanamine solution having a concentration of 20 g / L, wherein the pH of the acidic polyurea-polyguanamine solution is 7, and a three-dimensional composite aerogel having a positively charged nanofiltration layer on the surface is obtained by electrostatic crosslinking, wherein the nanofiltration layer has a thickness of 100 μm and a pore size of less than 2 nm; The method for preparing polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose in S1 comprises the following steps: S11. 4-acetylamino-TEMPO oxidized nanocellulose, polyaspartic acid and N-hydroxysuccinimide in a mass ratio of 8:3:0.015 are added to water, and a homogeneous solution A with a mass fraction of 10 wt % is obtained by stirring; S12. Add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to solution A. The mass of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 115wt% of the 4-acetylamino-TEMPO oxidized nanocellulose in S11. Adjust the pH value of the solution to 6 at room temperature. After reacting for 7 hours, wash and freeze-dry to obtain polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose. Example 3 A material for deep treatment of urban sewage, characterized in that: the material is a three-dimensional composite aerogel, the surface of the three-dimensional composite aerogel has a positively charged nanofiltration layer, the nanofiltration layer is obtained by electrostatic crosslinking of polyacrylamide and polyurea-polyguanamine, the three-dimensional composite aerogel uses polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide as a skeleton, the polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose is a two-dimensional network structure, and the skeleton is loaded with calcium hydroxide and magnesium hydroxide nanosheets; The method for preparing the three-dimensional composite aerogel comprises the following steps: S1. adding polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide in a mass ratio of 4:1 to water, and stirring to obtain a homogeneous solution with a mass fraction of 12 wt %; S2. Add limestone tailing particles with a particle size of 300 nm to the solution obtained in S1, wherein the mass of the ball-milled limestone tailing is 12 wt % of the polyaspartic acid-grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide, and add an ammonia solution to adjust the solution pH to 8, and obtain a mixed solution by ultrasonic dispersion; S3. freeze-dry the solution obtained in S2 at -45 °C for 20 h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 is immersed in an acidic polyurea-polyguanamine solution having a concentration of 15 g / L, wherein the pH of the acidic polyurea-polyguanamine solution is 6, and a three-dimensional composite aerogel having a positively charged nanofiltration layer on the surface is obtained by electrostatic crosslinking, wherein the nanofiltration layer has a thickness of 80 μm and a pore size of less than 2 nm; The method for preparing polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose in S1 comprises the following steps: S11. 4-acetylamino-TEMPO oxidized nanocellulose, polyaspartic acid and N-hydroxysuccinimide in a mass ratio of 7:2:0.012 are added to water, and a homogeneous solution A with a mass fraction of 8 wt % is obtained by stirring; S12. Add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to solution A. The mass of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 13wt% of the 4-acetylamino-TEMPO oxidized nanocellulose in S11. Adjust the pH value of the solution to 4 at room temperature. After reacting for 5 hours, wash and freeze-dry to obtain polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose. Example 4 A material for deep treatment of urban sewage, characterized in that: the material is a three-dimensional composite aerogel, the surface of the three-dimensional composite aerogel has a positively charged nanofiltration layer, the nanofiltration layer is obtained by electrostatic crosslinking of polyacrylamide and polyurea-polyguanamine, the three-dimensional composite aerogel uses polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide as a skeleton, the polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose is a two-dimensional network structure, and the skeleton is loaded with calcium hydroxide and magnesium hydroxide nanosheets; The method for preparing the three-dimensional composite aerogel comprises the following steps: S1. adding polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide in a mass ratio of 5:2 to water, and stirring to obtain a homogeneous solution with a mass fraction of 11 wt %; S2. Add limestone tailing particles with a particle size of 450 nm to the solution obtained in S1, wherein the mass of the ball-milled limestone tailing is 12 wt % of the polyaspartic acid-grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide, add sodium carbonate solution to adjust the solution pH to 8, and obtain a mixed solution by ultrasonic dispersion; S3. freeze-dry the solution obtained in S2 at -40 °C for 22 h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 is immersed in an acidic polyurea-polyguanamine solution having a concentration of 18 g / L, the pH of the acidic polyurea-polyguanamine solution is 6, and a three-dimensional composite aerogel having a positively charged nanofiltration layer on the surface is obtained by electrostatic crosslinking, wherein the nanofiltration layer has a thickness of 70 to 100 μm and a pore size of less than 2 nm; The method for preparing polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose in S1 comprises the following steps: S11. adding 4-acetylamino-TEMPO oxidized nanocellulose, polyaspartic acid and N-hydroxysuccinimide in a mass ratio of 7:2:0.01 to water, and stirring to obtain a homogeneous solution A with a mass fraction of 8 wt %; S12. Add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to solution A. The mass of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 13wt% of the 4-acetylamino-TEMPO oxidized nanocellulose in S11. Adjust the pH value of the solution to 5 at room temperature. After reacting for 5 hours, wash and freeze-dry to obtain polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose. Example 5 A material for deep treatment of urban sewage, characterized in that: the material is a three-dimensional composite aerogel, the surface of the three-dimensional composite aerogel has a positively charged nanofiltration layer, the nanofiltration layer is obtained by electrostatic crosslinking of polyacrylamide and polyurea-polyguanamine, the three-dimensional composite aerogel uses polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide as a skeleton, the polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose is a two-dimensional network structure, and the skeleton is loaded with calcium hydroxide and magnesium hydroxide nanosheets; The method for preparing the three-dimensional composite aerogel comprises the following steps: S1. adding polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide in a mass ratio of 1:1 to water, and stirring to obtain a homogeneous solution with a mass fraction of 10 wt%; S2. Add limestone tailing particles with a particle size of 550 nm to the solution obtained in S1, wherein the mass of the ball-milled limestone tailing is 14 wt % of the polyaspartic acid-grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide, add sodium bicarbonate solution to adjust the solution pH to 7, and obtain a mixed solution by ultrasonic dispersion; S3. freeze-dry the solution obtained in S2 at -45 °C for 22 h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 is immersed in an acidic polyurea-polyguanamine solution having a concentration of 15 g / L, wherein the pH of the acidic polyurea-polyguanamine solution is 5, and a three-dimensional composite aerogel having a positively charged nanofiltration layer on the surface is obtained by electrostatic crosslinking, wherein the nanofiltration layer has a thickness of 80 μm and a pore size of less than 2 nm; The method for preparing polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose in S1 comprises the following steps: S11. 4-acetylamino-TEMPO oxidized nanocellulose, polyaspartic acid and N-hydroxysuccinimide in a mass ratio of 7:2:0.012 are added to water, and a homogeneous solution A with a mass fraction of 8 wt % is obtained by stirring; S12. Add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to solution A. The mass of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 12wt% of the 4-acetylamino-TEMPO oxidized nanocellulose in S11. Adjust the pH value of the solution to 5 at room temperature. After reacting for 6 hours, wash and freeze-dry to obtain polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose. Example 6 A material for deep treatment of urban sewage, characterized in that: the material is a three-dimensional composite aerogel, the surface of the three-dimensional composite aerogel has a positively charged nanofiltration layer, the nanofiltration layer is obtained by electrostatic crosslinking of polyacrylamide and polyurea-polyguanamine, the three-dimensional composite aerogel uses polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide as a skeleton, the polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose is a two-dimensional network structure, and the skeleton is loaded with calcium hydroxide and magnesium hydroxide nanosheets; The method for preparing the three-dimensional composite aerogel comprises the following steps: S1. adding polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide in a mass ratio of 4:1 to water, and stirring to obtain a homogeneous solution with a mass fraction of 8 wt %; S2. Add limestone tailing particles with a particle size of 580 nm to the solution obtained in S1, wherein the mass of the ball-milled limestone tailings is 13 wt % of the polyaspartic acid-grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide, and add an ammonia solution to adjust the solution pH to 7, and obtain a mixed solution by ultrasonic dispersion; S3. freeze-dry the solution obtained in S2 at -40 °C for 22 h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 is immersed in an acidic polyurea-polyguanamine solution having a concentration of 15 g / L, wherein the pH of the acidic polyurea-polyguanamine solution is 6, and a three-dimensional composite aerogel having a positively charged nanofiltration layer on the surface is obtained by electrostatic crosslinking, wherein the nanofiltration layer has a thickness of 90 μm and a pore size of less than 2 nm; The method for preparing polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose in S1 comprises the following steps: S11. adding 4-acetylamino-TEMPO oxidized nanocellulose, polyaspartic acid and N-hydroxysuccinimide in a mass ratio of 7:2:0.014 to water, and stirring to obtain a homogeneous solution A with a mass fraction of 2 to 10 wt %; S12. Add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to solution A. The mass of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 14wt% of the 4-acetylamino-TEMPO oxidized nanocellulose in S11. Adjust the pH value of the solution to 5 at room temperature. After reacting for 6 hours, wash and freeze-dry to obtain polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose. Example 7 A material for deep treatment of urban sewage, characterized in that: the material is a three-dimensional composite aerogel, the surface of the three-dimensional composite aerogel has a positively charged nanofiltration layer, the nanofiltration layer is obtained by electrostatic crosslinking of polyacrylamide and polyurea-polyguanamine, the three-dimensional composite aerogel uses polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide as a skeleton, the polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose is a two-dimensional network structure, and the skeleton is loaded with calcium hydroxide and magnesium hydroxide nanosheets; The method for preparing the three-dimensional composite aerogel comprises the following steps: S1. adding polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide in a mass ratio of 4:3 to water, and stirring to obtain a homogeneous solution with a mass fraction of 4 to 12 wt %; S2. Add limestone tailing particles with a particle size of 350 nm to the solution obtained in S1, wherein the mass of the ball-milled limestone tailing is 12 wt % of the polyaspartic acid-grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide, add sodium bicarbonate solution to adjust the solution pH to 7, and obtain a mixed solution by ultrasonic dispersion; S3. freeze-dry the solution obtained in S2 at -48°C for 18 h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 is immersed in an acidic polyurea-polyguanamine solution having a concentration of 12 g / L, wherein the pH of the acidic polyurea-polyguanamine solution is 5, and a three-dimensional composite aerogel having a positively charged nanofiltration layer on the surface is obtained by electrostatic crosslinking, wherein the nanofiltration layer has a thickness of 90 μm and a pore size of less than 2 nm; The method for preparing polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose in S1 comprises the following steps: S11. adding 4-acetylamino-TEMPO oxidized nanocellulose, polyaspartic acid and N-hydroxysuccinimide in a mass ratio of 7:3:0.014 to water, and stirring to obtain a homogeneous solution A with a mass fraction of 8 wt %; S12. Add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to solution A. The mass of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 14wt% of the 4-acetylamino-TEMPO oxidized nanocellulose in S11. Adjust the pH value of the solution to 5 at room temperature. After reacting for 5 hours, wash and freeze-dry to obtain polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose. Example 8 A material for deep treatment of urban sewage, characterized in that: the material is a three-dimensional composite aerogel, the surface of the three-dimensional composite aerogel has a nanofiltration layer with a positive charge, the nanofiltration layer is obtained by electrostatic crosslinking of polyacrylamide and polyurea-polyguanamine, the three-dimensional composite aerogel uses polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide as a skeleton, the polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose is a two-dimensional network structure, and the skeleton is loaded with calcium hydroxide and magnesium hydroxide nanosheets; The method for preparing the three-dimensional composite aerogel comprises the following steps: S1. adding polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide in a mass ratio of 5:2 to water, and stirring to obtain a homogeneous solution with a mass fraction of 8 wt %; S2. Add limestone tailing particles with a particle size of 350 nm to the solution obtained in S1, wherein the mass of the ball-milled limestone tailing is 10 to 15 wt % of the polyaspartic acid-grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide, add an ammonia solution to adjust the solution pH to 7 to 8, and obtain a mixed solution by ultrasonic dispersion; S3. freeze-dry the solution obtained in S2 at -44°C for 20 h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 is immersed in an acidic polyurea-polyguanamine solution having a concentration of 15 g / L, wherein the pH of the acidic polyurea-polyguanamine solution is 5 to 7, and a three-dimensional composite aerogel having a positively charged nanofiltration layer on the surface is obtained by electrostatic crosslinking, wherein the nanofiltration layer has a thickness of 75 μm and a pore size of less than 2 nm; The method for preparing polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose in S1 comprises the following steps: S11. 4-acetylamino-TEMPO oxidized nanocellulose, polyaspartic acid and N-hydroxysuccinimide in a mass ratio of 7:2:0.013 are added to water, and a homogeneous solution A with a mass fraction of 8 wt % is obtained by stirring; S12. Add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to solution A. The mass of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 13wt% of the 4-acetylamino-TEMPO oxidized nanocellulose in S11. Adjust the pH value of the solution to 5 at room temperature. After reacting for 4 hours, wash and freeze-dry to obtain polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose. Example 9 A material for deep treatment of urban sewage, characterized in that: the material is a three-dimensional composite aerogel, the surface of the three-dimensional composite aerogel has a positively charged nanofiltration layer, the nanofiltration layer is obtained by electrostatic crosslinking of polyacrylamide and polyurea-polyguanamine, the three-dimensional composite aerogel uses polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide as a skeleton, the polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose is a two-dimensional network structure, and the skeleton is loaded with calcium hydroxide and magnesium hydroxide nanosheets; The method for preparing the three-dimensional composite aerogel comprises the following steps: S1. adding polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide in a mass ratio of 1 to 5:1 to 3 to water, and stirring to obtain a homogeneous solution with a mass fraction of 7 wt %; S2. Add limestone tailing particles with a particle size of 380 nm to the solution obtained in S1, wherein the mass of the ball-milled limestone tailings is 14 wt % of the polyaspartic acid-grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide, add sodium bicarbonate solution to adjust the solution pH to 7, and obtain a mixed solution by ultrasonic dispersion; S3. freeze-dry the solution obtained in S2 at -48°C for 24h to obtain an initial aerogel; S4. The initial aerogel obtained in S3 is immersed in an acidic polyurea-polyguanamine solution having a concentration of 15 g / L, wherein the pH of the acidic polyurea-polyguanamine solution is 6, and a three-dimensional composite aerogel having a positively charged nanofiltration layer on the surface is obtained by electrostatic crosslinking, wherein the nanofiltration layer has a thickness of 95 μm and a pore size of less than 2 nm; The method for preparing polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose in S1 comprises the following steps: S11. adding 4-acetylamino-TEMPO oxidized nanocellulose, polyaspartic acid and N-hydroxysuccinimide in a mass ratio of 7:3:0.013 to water, and stirring to obtain a homogeneous solution A with a mass fraction of 8 wt %; S12. Add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to solution A. The mass of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride is 14wt% of the 4-acetylamino-TEMPO oxidized nanocellulose in S11. Adjust the pH value of the solution to 4 at room temperature. After reacting for 4 hours, wash and freeze-dry to obtain polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose. Comparative Example 1 The difference between Comparative Example 1 and Example 3 is that the three-dimensional aerogel is not immersed in the acidic polyurea-polyguanamine solution, and no nanofiltration layer is formed on its surface. Comparative Example 2 The difference between Comparative Example 1 and Example 6 is that 4-acetylamino-TEMPO oxidized nanocellulose is not grafted with polyaspartic acid. Comparative Example 3 The difference between Comparative Example 3 and Example 7 is that no Mg-HA nanosheets are loaded on the three-dimensional aerogel skeleton. Comparative Example 4 The difference between Comparative Example 4 and Example 9 is that in S2, HA nanosheets are directly added to the solution obtained in S1 without adding limestone tailings particles. Performance Testing Table 1 Removal rate of negatively charged pollutants in urban sewage Table 2 Removal rate of metal ions in urban sewage Note: Sodium dodecylbenzene sulfonate is used in Table 1 to represent anionic surfactants. Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A material for deep treatment of urban sewage, characterized in that: The material is a three-dimensional composite aerogel, the surface of the three-dimensional composite aerogel has a nanofiltration layer with a positive charge, the nanofiltration layer is obtained by electrostatic crosslinking of polyacrylamide and polyurea-polyguanamine, the three-dimensional composite aerogel uses 4-acetylamino-TEMPO oxidized nanocellulose grafted with polyaspartic acid and polyacrylamide as a skeleton, the 4-acetylamino-TEMPO oxidized nanocellulose grafted with polyaspartic acid is a two-dimensional network structure, and the skeleton is loaded with calcium hydroxide and magnesium hydroxide nanosheets.
2. The method for preparing a material for deep treatment of urban sewage according to claim 1, characterized in that: The preparation method of the three-dimensional composite aerogel comprises the following steps: S1. adding polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide into water, and stirring the solution to homogenize; S2. Add the ball-milled limestone tailing particles to the solution obtained in S1, add an alkaline solution to adjust the pH of the solution to 7-8, and obtain a mixed solution by ultrasonic dispersion; S3. freeze-drying the solution obtained in S2 to obtain an initial aerogel; S4. The initial aerogel obtained in S3 is immersed in an acidic polyurea-polyguanamine solution, and a three-dimensional composite aerogel having a positively charged nanofiltration layer on the surface is obtained by electrostatic crosslinking.
3. The method for preparing a material for deep treatment of urban sewage according to claim 2, characterized in that: The mass ratio of the polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose to polyacrylamide in S1 is 1-5:1-3, and the mass fraction of the homogeneous solution is 4-12 wt %.
4. The method for preparing a material for deep treatment of urban sewage according to claim 2, characterized in that: The preparation method of polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose in S1 comprises the following steps: S11. adding 4-acetylamino-TEMPO oxidized nanocellulose, polyaspartic acid and N-hydroxysuccinimide to water, and stirring to obtain a homogeneous solution A; S12. Add 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride to solution A, adjust the pH value of the solution to 4-6 at room temperature, react for 3-7 hours, wash and freeze-dry, and obtain polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose.
5. The method for preparing a material for deep treatment of urban sewage according to claim 4, characterized in that: The mass ratio of 4-acetylamino-TEMPO oxidized nanocellulose, polyaspartic acid and N-hydroxysuccinimide in S11 is 6-8:2-3:0.01-0.015, and the mass fraction of the homogeneous solution is 2-10wt%.
6. The method for preparing a material for deep treatment of urban sewage according to claim 4, characterized in that: The mass of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride in S12 is 10-15wt% of the 4-acetylamino-TEMPO oxidized nanocellulose in S11.
7. The method for preparing a material for deep treatment of urban sewage according to claim 2, characterized in that: The particle size of the ball-milled limestone tailings in S2 is 300-600 nm, the mass of the ball-milled limestone tailings is 10-15 wt % of the polyaspartic acid grafted 4-acetylamino-TEMPO oxidized nanocellulose and polyacrylamide, and the alkaline solution is one or more of sodium bicarbonate solution, sodium carbonate solution or ammonia solution.
8. The method for preparing a material for deep treatment of urban sewage according to claim 2, characterized in that: The freeze drying temperature in S3 is -50 to -40°C and the time is 18 to 24 hours.
9. The method for preparing a material for deep treatment of urban sewage according to claim 2, characterized in that: The concentration of the acidic polyurea-polyguanamine solution in S4 is 5-20 g / L, the pH of the acidic polyurea-polyguanamine solution is 5-7, the thickness of the nanofiltration layer is 70-100 μm, and the pore size is less than 2 nm.
Citation Information
Patent Citations
Microbial immobilized fungicide for treating high-nitrogen wastewater and preparation method of microbial immobilized fungicide
CN108795922A
Preparation method of MOF (Metal Organic Framework) loaded aerogel for adsorbing VOCs (Volatile Organic Compounds)
CN113477234A
Carbon-based composite aerogel with fire early warning function and high compression performance and preparation method therefor
JP2023095841A
Fast and high-capacity intelligent cellulose-based oil-absorbing material and preparation method and use thereof
US11185796B1
Preparation method and application of cellulose / lignin / clay composite aerogel for highly efficient adsorption of antibiotics
US12049413B1